Investigation of duck plague virus in hoar areas of Bangladesh - Hossen, A; Rahman, MH; Ali, MZ; Yousuf, MA; Hassan, MZ; Giasuddin, M (Bangladesh Journal of Livestock Research, 2020)
Duck plague (DP) is the most important infectious disease of geese, ducks and free-ranging water birds. The present study was conducted to determine the prevalence of duck plague virus followed by isolation and identification. For these purposes, a total of 155 cloacal swabs samples were collected randomly from duck of different haor areas of Bangladesh including 45 (41 surveillance and 4 clinical) samples from Netrokona; 42 (40 surveillance and 2 clinical) samples from Kishoregonj; 30 samples from Brahmanbaria and 38 samples from Sunamganj. The samples were processed and pooled (1:5 ratio) for initial screening of target polymerase gene of duck plague virus by polymerase chain reaction (PCR) method. All the samples of a positive pool were then tested individually for identifying the individual positive samples. The result showed that out of 155 samples, 41 (26.45%) were found positive in which 17 were from Netrokona, where 15 (36.58%) were from surveillance samples and 2 (50%) were from clinical sample; 16 were from Kishoregonj, where 14 (35%) were from surveillance samples and 2 (100%) were from clinical sample; 2 (6.6%) were from Brahmanbaria and 5 (13.15%) were from Sunamganj. These positive samples were inoculated into 9-10 days embryonated duck eggs (EDE) through chorioallantoic membrane (CAM) route for the isolation of virus. The EDE died earlier was also chilled, and in a similar way, the CAMs were collected and again performed PCR for id entification of virus. Out of 41 PCR positive samples, 26 samples were isolated and reconfirmed by PCR. Subsequently, DPV was isolated in primary duck embryo fibroblasts cell culture and confirmed by observing cytopathic effect (CPE). Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 73-78